Room‐Temperature Phosphorescent Platinum(II) Alkynyls with Microsecond Lifetimes Bearing a Strong‐Field Pincer Ligand. Issue 38 (24th June 2020) - Liska, Tadeas; Swetz, Anna; Lai, Po‐Ni; Zeller, Matthias; Teets, Thomas S.; Gray, Thomas G.
Abstract: The use of organometallic triplet emitters in organic light emitting diodes (OLEDs) is motivated by the premise of efficient intersystem crossing leading to unit internal quantum efficiencies. However, since most devices are based on solid‐state components, an inherent limitation to square‐planar platinum(II) phosphors is their tendency toward aggregation‐based quenching. Here, a new class of emissive, four‐coordinate Pt II species based on the bisimidazolyl carbazolide (BIMCA) ligand is introduced, which displays highly efficient, long‐lived solid‐state phosphorescence at room temperature. A set of four BIMCAPt phenyl acetylides were synthesized that emit in the green ( λ max =507–540 nm) with >60 % quantum yield and millisecond lifetimes. The structures of the resulting species reveal a non‐planar structure imposed by steric clashes between BIMCA and the iodo or alkynyl co‐ligand. Ground‐state and photophysical characterization are presented. Density functional theory calculations indicate that the BIMCA ligand dominates the frontier orbitals along with the first Franck–Condon singlet and triplet excited states. Abstract : Positively glowing : The use of organometallic triplet emitters in OLEDs is motivated by the premise of efficient intersystem crossing leading to unit internal quantum efficiencies. Here, a new class of emissive, four‐coordinate Pt II species based on the bisimidazolyl carbazolide (BIMCA) ligand is introduced, which displays highly efficient, long‐lived solid‐state phosphorescence at room temperature.